2022
DOI: 10.1155/2022/9609559
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity and Antimicrobial Activity of Green Synthesized Silver Nanoparticles Using Nigella sativa Seeds on Wheat Seedlings

Abstract: Recently, the green synthesis of nanomaterials has grown in popularity and has become one of the most used approaches. Plant extracts are safe for the environment and could be cost-effective for nanoparticle preparation. Silver nanoparticles (AgNPs) have been synthesized using aqueous extracts of Nigella sativa (N. sativa) seeds. The formation of AgNPs was confirmed by using an X-ray diffractometer, a UV-visible spectrometer, and a transmission electron microscope. The phytotoxicity and genotoxicity of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
2
4
0
Order By: Relevance
“…As shown in Fig. 5 , the AgNPs displayed a single absorption peak in the UV spectrum at a specific nm, aligning with the findings of ( Elshazly et al, 2022 ). The stability of the freshly prepared AgNPs was assessed over 14 days in a suspended state in distilled water, with continuous monitoring of the distinct absorption peak in the spectrum.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As shown in Fig. 5 , the AgNPs displayed a single absorption peak in the UV spectrum at a specific nm, aligning with the findings of ( Elshazly et al, 2022 ). The stability of the freshly prepared AgNPs was assessed over 14 days in a suspended state in distilled water, with continuous monitoring of the distinct absorption peak in the spectrum.…”
Section: Resultssupporting
confidence: 86%
“…They are efficient against a variety of infections due to their broad-spectrum action, which lowers the possibility of resistance developing ( Saddik et al, 2021 , Abu-Dief et al, 2020 ). Additionally, it has been demonstrated that silver nanoparticles may successfully prevent and interfere with the formation of biofilms, which poses a serious problem for a number of industries, including healthcare and food processing ( Elshazly et al, 2022 ). Communities of bacteria known as biofilms are imprisoned in an extracellular polymeric matrix that they generate on their own, giving them remarkable resistance to conventional antimicrobial treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 ). The average particle size is determined to be 8.13 nm, which is compatible with the findings of SEM and TEM [ 32 , 33 ]. The structural and microstructural parameters were estimated, including lattice parameters, lattice spacing, respective reflections, and particle sizes [ 34 ].…”
Section: Resultssupporting
confidence: 76%
“…Miller’s indices (h k l) were evaluated according to their two-theta degree values, and they were found to be (1 1 1), (2 0 0), (2 2 0), and (3 1 2), corresponding to two-theta of values 37.9, 44.1, 64.2, and 77.2°, respectively. Thus, the XRD confirms the crystalline phase of the Ag NPs, and from the angle value, it is clear that the compound is stable [ 53 , 54 , 55 ]. The calculated average size of Ag NPs by the XRD line broadening method [ 56 ] was ~11.9 nm.…”
Section: Resultsmentioning
confidence: 94%